APPLICATION OF THE ANALYTICAL HIERARCHY PROCESS METHOD IN DETERMINING PRIORITY FOR APBDES ALLOCATION IN BONE VILLAGE, NEKAMESE SUBDISTRICT, KUPANG REGENCY - Widyastuti, Windy; Arthana, I Komang; Tungga, Cicilia A (Yayasan Pendidikan Cahaya Budaya Indonesia, 2025)
This study aims to apply the Analytical Hierarchy Process (AHP) method to determine the priority of using the Village Revenue and Expenditure Budget (APBDes) in Bone Village, Nekamese District, Kupang Regency. The background of the research is based on the challenges faced by the village government in managing the budget effectively amidst limited resources and numerous program proposals from the community. AHP was chosen for its ability to solve multi-criteria decision-making problems systematically and objectively. This research utilizes five main criteria: Health, Education, Food Security, Human Resource Quality, and Economy. Data were collected through interviews and questionnaires involving village officials and community members. The analysis results show that Health is the highest priority criterion. However, the selected alternative with the highest global weight is Road Construction, as it significantly contributes to all the criteria, including accessibility to health services. Therefore, the application of the AHP method proves effective in assisting the village government in setting development priorities that are more targeted, transparent, and accountable.